2023
DOI: 10.1093/sleep/zsad124
|View full text |Cite
|
Sign up to set email alerts
|

Global trends in the consumption of benzodiazepines and Z-drugs in 67 countries and regions from 2008 to 2018: a sales data analysis

Abstract: Study objectives To investigate the trends in the consumption of benzodiazepines (BZDs) and Z-drugs at global, regional, and national levels from 2008 to 2018, across 67 countries and regions. Methods This cross-sectional descriptive study investigated the consumption of BZDs and Z-drugs analysed by global pharmaceutical sales data from the IQVIA-Multinational Integrated Data Analysis System database between 2008 and 2018. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Our pilot study methodology was not structured to determine factors which might explain differences in the pattern of BZD use between the countries surveyed. However, a recent global analysis of BZD and ZD sales data found that increased consumption of these drugs in countries was statistically associated ( p < 0.05) with several factors including increased prevalence of anxiety, self-harm and neurological disorders ( 44 ). Other factors, such as differences in prescribers’ attitudes to the risks and benefits of long-term use of BZDs between countries may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Our pilot study methodology was not structured to determine factors which might explain differences in the pattern of BZD use between the countries surveyed. However, a recent global analysis of BZD and ZD sales data found that increased consumption of these drugs in countries was statistically associated ( p < 0.05) with several factors including increased prevalence of anxiety, self-harm and neurological disorders ( 44 ). Other factors, such as differences in prescribers’ attitudes to the risks and benefits of long-term use of BZDs between countries may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, difficulty in sleep can significantly comprises public health including psychiatric diseases, posing challenges for a substantial portion of the population [ 2 ]. In response to these sleep-related issues, the widespread use of hypnotics, especially benzodiazepines (BZDs), and Z-drug (ZD), has emerged as a common treatment [ 3 ]. Nevertheless, ongoing debates persist regarding the potential long-term consequences of prolonged hypnotics use on health [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%